Discourse and polemic in a political debate - Brandão, Helena H. Nagamine (Revista do Instituto de Estudos Brasileiros, 1994)
This article reveals aspects of the operation of the two forms of discourse in a polemical relationship: the spoken discourse of the two candidates in the last Brazilian Presidential election campaign (december/1989). The way that each discourse search for its identity and delineates its boundaries in an incessant effort of reciprocal delimitation is analyzed. In this article, the following items are verified: a) the strategies of discourse that each speaker mobilizes to represent himself and his adversary; and b) the strategies of enunciative modalization which characterize the "actancial" behaviour of each polemist.